Engineering of a near-infrared fluorescent probe for real-time simultaneous visualization of intracellular hypoxia and induced mitophagy. Issue 24 (24th May 2018) - Liu, Yongchao; Teng, Lili; Chen, Lanlan; Ma, Hongchang; Liu, Hong-Wen; Zhang, Xiao-Bing
Abstract : A near-infrared fluorescent probe has been developed for real-time simultaneous visualization of intracellular hypoxia and the subsequent induced mitophagy. Abstract : Mitophagy induced by hypoxia plays an important role in regulating cellular homeostasis via the removal of dysfunctional mitochondria in the lysosomal degradation pathway, which results in physiological changes in the mitochondria, such as the pH, polarity and viscosity. However, the lack of an effective method for imaging of both the hypoxic microenvironment and the resulting variable mitochondria limits the visualization of hypoxia-induced mitophagy. Based on the specific mitochondrial pH changes during the hypoxia-induced mitophagy process, we have reported a near-infrared fluorescent probe (NIR-HMA) for real-time simultaneous visualization of the hypoxic microenvironment and the subsequent mitophagy process in live cells. NIR-HMA selectively accumulated in the hypoxic mitochondria in the NIR-MAO form, emitting at 710 nm, and then transformed into NIR-MAOH, emitting at 675 nm, in the acidified mitochondria-containing autolysosomes. Importantly, by smartly tethering the hypoxia-responsive group to the hydroxyl group of the NIR-fluorochrome, which shows ratiometric pH changes, NIR-HMA can differentiate between different levels of the hypoxic microenvironment and mitophagy. Furthermore, using NIR-HMA, we could track the complete mitophagy process from the mitochondria to the autolysosomes and visualize mitophagy caused only by hypoxia both in cancer cells and normal cells. Finally, NIR-HMA was applied to investigate the role that mitophagy plays in the hypoxic microenvironment via the cycling hypoxia-reoxygenation model. We observed a decreased fluorescence ratio after reoxygenation and a further increased mitophagy level after hypoxia was induced again, suggesting that mitophagy might be a self-protective process that allows cells to adapt to hypoxia. Our work may provide an attractive way for real-time visualization of relevant physiological processes in hypoxic microenvironments.